Answer:
![\large\boxed{(x-2)^2+(y-1)^2=34}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4wquplfkeh2jajsseubmclcrgy17k9ggww.png)
Explanation:
The equation of a circle in standard form:
![(x-h)^2+(y-k)^2=r^2](https://img.qammunity.org/2020/formulas/mathematics/high-school/kmmm139x85fjht54s8zz0668styzp2e6cm.png)
(h, k) - center
r - radius
We have the endpoints of the diameter: (-1, 6) and (5, -4).
Midpoint of diameter is a center of a circle.
The formula of a midpoint:
![\left((x_1+x_2)/(2);\ (y_1+y_2)/(2)\right)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zywj8ljadio5p99xzov557rllta7lbb2wh.png)
Substitute:
![h=(-1+5)/(2)=(4)/(2)=2\\\\k=(6+(-4))/(2)=(2)/(2)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/x1s4z2hg4o3xk9rmkv1rlhm7m0ciwr6jv1.png)
The center is in (2, 1).
The radius length is equal to the distance between the center of the circle and the endpoint of the diameter.
The formula of a distance between two points:
![d=√((x_2-x_1)^2+(y_2-y_1)^2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jq23b7gn8a5hqb5oj8gmcxlbivj810cso4.png)
Substitute the coordinates of the points (2, 1) and (5, -4):
![r=√((5-2)^2+(-4-1)^2)=√(3^2+(-5)^2)=√(9+25)=√(34)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4r4evmnysxaanb7ktgs92mi9h9elsi1ulg.png)
Finally we have:
![(x-2)^2+(y-1)^2=(√(34))^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yvb21e7ni07j4o7acs5qt3qvhsdufeeqq4.png)